Assessing Turkey's middle power foreign policy in MIKTA: Goals, means, and impact. (December 2016) - Dal, Emel Parlar; Kurşun, Ali Murat
This study attempts to identify possible new roles for intermediary actors in the changing global architecture by focusing on Turkey's middle power capacity in the nascent middle power network of Mexico, Indonesia, South Korea, Turkey, Australia (MIKTA). It looks at an overarching embedded analytical triad of goals, means, and impact, superimposed over positional, behavioural, and ideational sublayers. It tests the assumption that the more a state holds together its middle power goals, means, and impact in a combined way, the more leverage it can have as a middle power in the changing international political economy. After reviewing the existing literature on middle powers, the first part of this paper outlines this embedded analytical framework. The second and the third parts seek to operationalize this framework, in particular at institutional and state levels in the example of MIKTA and Turkey. The fourth part delves into the opportunities and challenges that Turkey faces in its MIKTA trajectory (in the light of the conclusions drawn from the second and third parts). The study concludes that while Turkey possesses fairly compatible goals and impact with those of MIKTA, it is still far from channelling all of its capabilities to this new network due mainly to the domestic and regional impediments it faces—as well as the lack of a comprehensive roadmap in relation to MIKTA.